Assessment of cognitive performance and fatigability in elite athletes: Short and portable protocols for field monitoring under hypoxia - Giorgio Varesco; Nicolas Bourrel; François Bieuzen; Guido Simonelli (PLoS ONE, 2026)
Purpose This study aimed to evaluate whether short (~15 min) cognitive protocols can detect fatigability in normoxia versus normobaric hypoxia in elite youth athletes, using tasks directly transferable to the field. Methods Elite youth mogul skiers (18 ± 2 y) completed two studies. In Study I, 17 athletes (7 women) performed a cognitive test after a repeated tuck-jump protocol designed to mimic mid-training physical demands under two conditions in fixed order: sham normoxia (simulated 200 m) and normobaric hypoxia (3500 m, blood saturation ~88%). In Study II, 16 athletes (6 women) performed the same cognitive test without the jump task, with conditions randomized. In both studies, response time and accuracy during a 10-min color Multisource Interference Task (cMSIT) were used to assess cognitive performance, and a 3-min Psychomotor Vigilance Task (PVT) was administered before and after the cMSIT to quantify fatigability. Cognitive tests were performed on portable tablet devices. Results After adjusting for baseline cognitive performance, cMSIT response time was greater in hypoxia than in normoxia in both Study I (10 ± 2%, p = 0.004) and Study II (4 ± 1%, p < 0.001). Accuracy remained high and similar across conditions in both studies (Study I: 96 ± 3%; Study II: 96 ± 0.5%; p > 0.09). In Study I, PVT response time increased only in hypoxia, from 363 ± 74 ms to 375 ± 89 ms (p = 0.021), and lapses increased from 1 ± 0.5 to 3 ± 2.5 (p < 0.001), whereas lapses remained unchanged in normoxia and in Study II (p > 0.82). In Study I, jump task performance showed a condition×set interaction (p = 0.048), with lower performance in the third set in hypoxia (19806 ± 2464 N·s) than in normoxia (20130 ± 3016 N·s; p = 0.012). Conclusions In elite youth athletes, hypoxemia reduces cognitive performance and could lead to increased fatigability. Importantly, hypoxia-related impairments are detectable with short portable cognitive assessments, which are promising tools for field monitoring, particularly when tasks combines cognitive and physical demands.